„Instruments of the Old Faith”: Magical Words in Three Medieval South Slavic Healing Rites for Snakebite - Kier, Andrew James (Poznańskie Studia Slawistyczne, 2012)
The line between Orthodox Christianity and pagan/folk customs and beliefs in the fifteenth century Slavia Orthodoxa was not precisely drawn. The population called upon spiritual forces of all kinds, to heal illnesses and injuries. Though the official position of the Orthodox Christian Church was to condemn and suppress these pre-Christian beliefs, certain elements such as magical words were included in Church-sanctioned texts. The fifteenth-century South Slavic trebnik (Hilandar HM.SMS.378) is one example of such a text. In addition to its canonical material, it contains a healing rite for a snakebite, which blends Orthodox Christian elements and pre-Christian ones, utilizing magical words. In this article, I examine Hilandar HM.SMS.378 – the magical words, the symbolism, and the cultural background – and compare it with two similar rites from a medieval South Slavic lječebnik (‘book of healing’) transcribed by V. Jagićin 1878. I also discuss the possibility that the three rites share a common origin.